(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In this article, the main purpose of teaching students in the middle school to clarify personal skills of every student, giving them proper education, life enhancing innovative technological world. Principal goal is to teach students to speak fluently in English, writing and reading comprehension skills.